Logistics clusters: The impact of further agglomeration, training and firm size on collaboration and value added services (2016)
Collaboration and the provision of value added services are key benefits for companies located within logistics clusters. We hypothesize that within the context of logistics clusters, further agglomeration within the more defined logistics parks and the availability of training opportunities enhance those benefits. We control for the effect of firm size in the projected relationships and propose that firm size positively impacts the degree of benefits obtained. Based on data from a survey conducted in the Zaragoza (Spain) Logistics Cluster, and using structural equation modeling, we demonstrate that further agglomeration into a logistics park positively impacts collaboration, and more specifically transportation capacity sharing. We also demonstrate that training positively impacts collaboration between cluster residents, both in terms of transportation capacity sharing and resource sharing, as well as the provision of value added services. These causal relationships are the same for big and small firms. Finally, we confirm that larger firms show higher levels of collaboration and value added services. Implications for managers and policy makers are provided.